Assessment of E-Procurement of Construction Products and Services - Irmawaty Tjan; Abdul Hadi Sirat; Suwito; Muhammad Syafi'i A. Basalamah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
According to Presidential Regulation No. 54 of 2010 governing Procurement of Government goods/services and its revisions, this research seeks to assess the efficacy of e-Procurement using e-Tendering procedures. Qualitative methods were used in this investigation. The information was gathered through conducting in-depth interviews with members of the procurement committee, as well as providers, companies, and relevant documents. Descriptive case and context analysis is employed for this analysis. The review of the e-procurement implementation at the North Maluku PUPR Construction Services selection implementation center revealed that the process had gone smoothly. This is evident from the study of e-several procurement's dimensions and the various means through which its goals might be attained. Presidential Regulation No. 4 of 2015 governs the use of e-Procurement. Human resources in the Working Group were found to be a positive factor in terms of e-viability Procurement's in this study's findings, while a lack of socialization, a dearth of LPSE human resources, an absence of training, inadequate infrastructure, frequent updates to the SPSE application's version, a lack of regional regulations governing the electronic procurement of goods and services, and a lack of funding were found to be negative factors.